2017
DOI: 10.1002/adfm.201704726
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Cubic Mesoporous Silica as a Non‐Chemodosimetric Fluorescence Probe and Adsorbent for Selective Detection and Removal of Bisulfite Anions along with Toxic Metal Ions

Abstract: Dual signaling and remediation systems for detection and adsorption of toxic analytes have gained more attention over sensory probes only. However, most of the sensors for bisulfites are chemodosimetric probes, which are irreversible and having drawbacks of absolute selectivity, recyclability, and solubility in a pure aqueous system. To address above drawbacks a new non‐chemodosimetric probe material with a strong hydrogen bonding pocket for bisulfites is developed. Synthesis of cubic mesoporous silica by a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 131 publications
1
54
0
Order By: Relevance
“…Copyright 2019, Wiley. E) Structure of cubic MSNs‐AZB‐3, relative emission intensity (λ em = 510 nm) with various metal ions (160 × 10 −6 m ), Reproduced with permission . Copyright 2018, Wiley.…”
Section: Sio2‐based Hybrid Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copyright 2019, Wiley. E) Structure of cubic MSNs‐AZB‐3, relative emission intensity (λ em = 510 nm) with various metal ions (160 × 10 −6 m ), Reproduced with permission . Copyright 2018, Wiley.…”
Section: Sio2‐based Hybrid Materialsmentioning
confidence: 99%
“…Very recently, a nonchemodosimetric fluorescence hybrid probe (MSNs‐AZB‐3) was reported by Chatterjee et al for the selective detection and adsorption of toxic metal ions (Hg 2+ , Cd 2+ , Cu 2+ , and Zn 2+ ) and bisulfite anions in aqueous solutions (Figure E), which represents the first example of a nonchemodosimetric fluorescence hybrid material for selective bisulfite anions detection and adsorption. MSNs‐AZB‐3 showed an immediate fluorescence quenching response at 510 nm (λ em ) toward Hg 2+ , Cd 2+ , Cu 2+ , Zn 2+ , and HSO 3 − (160 × 10 −6 m ) with detection limits of 126, 95, 14, 27, and 64 ppb, respectively, in suspended aqueous solution (0.25 mg mL −1 ) at neutral pH (∼7).…”
Section: Sio2‐based Hybrid Materialsmentioning
confidence: 99%
“…In the past, extensive studies have been reported to unravel the scopeo fs uch functional materials as activated porous carbon, [5] zeolites, [6] silica particles, [7][8][9][10][11][12][13] graphene oxide, [14,15] metals or metal oxides, [16,17] natural minerals [18][19][20] etc. as adsorbents for remediationo fm etal ions from water.T he search for new and efficient adsorbentsh as prompted the design and synthesis of functional polymers, [21][22][23][24][25][26][27] metal organic frameworks, [28][29][30] polymeric composites [31][32][33] and biohybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Some conventional analysis methods have been applied to the determination and quantification of Cu 2+ , including inductively coupled plasma, anodic stripping voltammetry, chromatography, electrochemical and atomic absorption spectrometry . These methods can accurately determine the concentration of trace Cu 2+ , but they also have some obvious shortcomings such as time‐consuming, high‐cost, complicated operation, and so on . Recently, the selective detection of trace Cu 2+ through fluorescence techniques has aroused great interest in many areas .…”
Section: Introductionmentioning
confidence: 99%